2013
DOI: 10.1093/ndt/gft485
|View full text |Cite
|
Sign up to set email alerts
|

Can aminotransferase-to-platelet ratio index and other non-invasive markers effectively reduce liver biopsies for renal transplant evaluation of hepatitis C virus-positive patients?

Abstract: Our data suggest that there may not currently be a simple and sufficiently accurate non-invasive test to replace liver biopsy in renal transplant workup for HCV-positive patients. The risks outweigh the benefits when it comes to using non-invasive markers like the APRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…In patients with chronic VHC, FIB4 was found to be better than APRI in evaluating F [31]. Studies on HD patients showed that the major strength of APRI was to exclude significant F, and only 50 % of the patients could be correctly diagnosed [14,28,30]. The assessment of biochemical indices in this patient population could be potentially altered because aminotransferase activity is usually lower in HD patients compared with non-uremic patients [32].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In patients with chronic VHC, FIB4 was found to be better than APRI in evaluating F [31]. Studies on HD patients showed that the major strength of APRI was to exclude significant F, and only 50 % of the patients could be correctly diagnosed [14,28,30]. The assessment of biochemical indices in this patient population could be potentially altered because aminotransferase activity is usually lower in HD patients compared with non-uremic patients [32].…”
Section: Discussionmentioning
confidence: 97%
“…This was a prospective multicenter transversal and observational study, which included 52 ESRD patients with (14) chronic viral hepatitis B (VHB) and (38) C (VHC) (age: 55.57 ± 14.46 years, dialysis vintage: 132.59 ± 86.02 months) and a control group of 26 patients with ESRD treated by HD, without chronic viral liver disease.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…These non-invasive tests have been validated neither in hemodialysis patients nor in kidney transplant recipients, given that they are less accurate than in the general population [17][18][19][20]. The assessment of liver stiffness by elastography is imperfect in this population, even if it is superior in staging the severity of hepatic fibrosis, compared with biochemical markers [20,21].…”
Section: Non-invasive Markers Of Fibrosis and Liver Biopsy In Evaluatmentioning
confidence: 99%